The academic achievement of elite athletes at Australian schools - Georgakis, S.; Evans, L. R.; Warwick, L. (Journal of Education and Training Studies, 2015)
While sport and student-athletes have featured in the Australian education system since compulsory schooling, there has been no analysis to date of the link between academic achievement and elite student-athletes. However, this is in stark contrast to the United States of America (US), where student-athletes have been the subject of sustained research and examination. In order to rectify this neglected area of research in the Australian context, this study investigated the Higher School Certificate (HSC) results of 641 Combined High School (CHS) Blues recipients over 11 years from 2001 until 2011, comparing them with the performance of the total general HSC population over the same period. The HSC summary aggregate data for Blues recipients was examined for 15 subjects, plus gender and sport. School Index of Community Socio-Economic Advantage (ICSEA) value also formed part of the analysis. The results demonstrated the student-athletes performed at levels similar to, or better than, their peers. Their performance was notably superior in some subjects such as Personal Development, Health and Physical Education (PDHPE). In particular, female Blues performed at higher levels than male Blues, across the range of subjects. Female Blues also generally outperformed the general HSC population. Analysis of individual Blues sports suggests that swimming produced a disproportionate number of high attainers. The findings suggest that despite their heavy sporting commitments and necessarily demanding training timetables, the sampled elite student-athletes performed at levels equal to, or better than, their peers.